Efficacy of orthopedic treatment with protraction facemask on skeletal Class III malocclusion: a systematic review and meta‐analysis. (14th April 2014) - Cordasco, G.; Matarese, G.; Rustico, L.; Fastuca, S.; Caprioglio, A.; Lindauer, S. J.; Nucera, R.
Abstract The objective of this systematic review was to estimate the efficacy of protraction facemask on the correction of Class III malocclusion in the short term. A systematic review of articles was performed using different electronic databases (PubMed, Ovid, Cochrane Central Register of Controlled Trials, Web of Science, LILACS, and Google Scholar). Search terms comprised 'orthopedic treatment' and 'Class III malocclusion'. The selection criteria were set in order to include in this review only randomized clinical trials (RCTs) performed treating with facemask Class III growing patients. Studies' selection, data extraction, and risk of bias's assessment were executed independently by two authors using pre‐defined data forms. All pooled analyses of data were based on random effects models. A pre‐specified subgroup analysis was planned to evaluate the effect of preliminary rapid palatal expansion on facemask efficacy. Three RCTs met our inclusion criteria. In total, data from 155 patients (92 treated and 63 controls) were collected. The treated group showed the following significant changes: ANB° +3.66° [95%CI (2.58, 4.74)]; SNA° +2.10 [95%CI (1.14, 3.06)]; SNB° −1.54 [95%CI (−2.13, −0.95)]; SN‐palatal plane −0.82° [95%CI (−1.62, −0.02)]; and SN‐mandibular plane +1.51 [95%CI (0.61, 2.41)]. Heterogeneity varied from low to moderate (mean I2 value: 41.4 ± 20.8). Facemask is effective correcting Class III malocclusion in the short term. The skeletal modifications induced by facemask are forward displacement of maxilla, backward displacement of mandible, clockwise rotation of the mandibular plane, and counterclockwise rotation of the maxillary plane.